Advances in Understanding Human Genetic Variations That Influence Innate Immunity to Fungi - Merkhofer, Richard M.; Klein, Bruce S. (Frontiers in Cellular and Infection Microbiology, 2020)
Fungi are ubiquitous. Yet, despite our frequent exposure to commensal fungi of the normal mammalian microbiota and environmental fungi, serious, systemic fungal infections are rare in the general population. Few, if any, fungi are obligate pathogens that rely on infection of mammalian hosts to complete their lifecycle; however, many fungal species are able to cause disease under select conditions. The distinction between fungal saprophyte, commensal, and pathogen is artificial and heavily determined by the ability of an individual host's immune system to limit infection. Dramatic examples of commensal fungi acting as opportunistic pathogens are seen in hosts that are immune compromised due to congenital or acquired immune deficiency. Genetic variants that lead to immunological susceptibility to fungi have long been sought and recognized. Decreased myeloperoxidase activity in neutrophils was first reported as a mechanism for susceptibility to Candida infection in 1969. The ability to detect genetic variants and mutations that lead to rare or subtle susceptibilities has improved with techniques such as single nucleotide polymorphism (SNP) microarrays, whole exome sequencing (WES), and whole genome sequencing (WGS). Still, these approaches have been limited by logistical considerations and cost, and they have been applied primarily to Mendelian impairments in anti-fungal responses. For example, loss-of-function mutations in CARD9 were discovered by studying an extended family with a history of fungal infection. While discovery of such mutations furthers the understanding of human antifungal immunity, major Mendelian susceptibility loci are unlikely to explain genetic disparities in the rate or severity of fungal infection on the population level. Recent work using unbiased techniques has revealed, for example, polygenic mechanisms contributing to candidiasis. Understanding the genetic underpinnings of susceptibility to fungal infections will be a powerful tool in the age of personalized medicine. Future application of this knowledge may enable targeted health interventions for susceptible individuals, and guide clinical decision making based on a patient's individual susceptibility profile.